Spectroscopic Study of the Interaction of Amino Acids with Copper(II) Ions in Aqueous Solution - SARMA, K.G.; SARMA, RAMAN (Asian Journal of Chemistry, 2010)
The interactions of copper(II) ions with some essential amino acids viz., L-leucine(Leu), L-glycylglycine (Gly.gly), L-methionine (meth), L-lysine (Lys) have been studied in aqueous solution at different temperatures by visible spectrophotometric method. The equilibrium constants of the process. [Cu(H2O)4]2+ + L = [Cu(H2O)3L]2+ + H2O (where L stands for the monodentate amino acid) have been determined and the thermodynamic parameters i.e., ΔGº, ΔHº and ΔSº have been calculated.